Application of CFD Simulations to Marine Hydrodynamic Problems (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Computational fluid dynamics (CFD) methods play important roles for the design and ability assessment of marine vehicles, structures, ships, etc. They are widely used in the fields of naval architecture and ocean engineering. Nowadays, CFD techniques have developed to a very high level. They can partly or even fully replace experiments in many cases. This Special Issue aims to collect the cutting-edge developments in the fundamentals and applications of CFD methods, which can promote the discussion and developing of the new CFD methods.